2020
DOI: 10.3390/ani10020366
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pseudorabies Virus in Wild Boar Foetus

Abstract: Pseudorabies, or Aujeszky’s disease, is a notifiable worldwide infection of domestic and feral swine that causes economic losses for the swine industry. In domestic pigs, the virus is responsible for nervous and/or respiratory symptoms; in pregnant sows, it is one of the major causes of stillbirth, mummification, embryonic death, and infertility (SMEDI). It is known that PRV infection in wild boar is associated with low pathogenicity and attenuated or absent symptomatology, but limited information is available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…This aspect represents a serious problem for agriculture and public health [ 15 , 16 ]. As for the latter, wild boar could act as a reservoir for different bacterial pathogens, contributing to maintaining and disseminating some important infectious diseases and zoonosis, including brucellosis [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This aspect represents a serious problem for agriculture and public health [ 15 , 16 ]. As for the latter, wild boar could act as a reservoir for different bacterial pathogens, contributing to maintaining and disseminating some important infectious diseases and zoonosis, including brucellosis [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wildlife acts as a reservoir for pathogens that contribute to maintaining and/or disseminating important infectious diseases [ 12 , 13 , 14 , 15 , 16 , 17 ]. Regarding Tuscany (Italy), among bacterial zoonoses, different etiological agents have been detected in wild animals, in particular Leptospira , Salmonella , Yersinia , and Listeria [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies previously conducted on the Italian wild boar population have revealed the presence of several pathogens, and among them, the viral agents responsible for reproductive disorders [ 10 , 15 , 46 , 70 , 78 , 79 , 80 ]. The present research has highlighted the circulation of SuHV-1, PCV2, and PPV1 in wild boar circulating in a research area located in central Italy.…”
Section: Discussionmentioning
confidence: 99%